Desain Formulasi Lumpur Untuk Pemboran Panas Bumi Di Sumur GG-01 - Nugroho Marsiyanto; Wahyu Sutresno; Berkah Hani (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
During the drilling process, we need to look at several aspects that need to be considered, including the drilling mud aspect which is one of the important aspects in a safe and efficient drilling process.The success of a drilling process through various rock layers is very dependent on the design of the drilling mud formulation. All of that can be influenced by the nature and physics of the drilling mud which needs to be adjusted to the formation conditions, formation pressure, rock type and fluid content contained in the formation. In designing the mud formulation that will be used, it can be done by using the mud system correlation method or by analyzing the pressure wells that become offset wells or key wells which are analyzed to determine the properties of the mud to be used. Well GG – 01 is an exploration well so it does not have an offset well. The drilling that will be penetrated is as many as 4 routes which in the first route the hole is made using a mash system so that it does not use drilling mud. And for the next route, the type of mud to be used is KCL Polymer with a different percentage on each route.